Práticas discursivas sobre sexualidade e religião de mulheres e homens com diagnóstico de esquizofrenia - Graupen, Andréa (2011)
In contemporary times, despite all the changes in mental health care in the last decades, it is observed that people diagnosed with schizophrenia are often labeled as being pathologically ill and suffered from social exclusion. Religiosity and sexuality are significant spheres of the human experience. They play an important role in the discursive practices of people experiencing psychological distress, tending to lead professionals and family in a negative way. Based on the theoretical-methodological framework of Critical Discourse Analysis, I interviewed seven patients, five women and two men, from an outpatient psychosocial care center, CAPS, located in Recife / PE. The aim of the research was to understand the discursive practices of the participants about the themes of sexuality and religion, also their articulation and perceptions of the differences of women and men s speech on the subject. In the group interviews, the discussion of the topic was generated from stimulus, using words related to sexuality and religion. In the Critical Discourse Analysis, the analytical framework used for the interpretation of the material produced during the interviews, the researcher s position clearly recognizes the power abuse experienced by the research subjects. The research practice may encourage the articulation of discursive practices as an alternative to the hegemonic discourses of "normality." In accordance to the Queer theories, this research has identify in the subject s statements a deconstruction of values, reproduced in preconceived terms in relation to sex, gender, normality and mental illness. The Christian tradition tends to shape the discursive practices of sexuality, even for those who are not particularly religious. This impact of Christian tradition is felt not only upon people diagnosed with schizophrenia. According to the literature review, the impact of Christian tradition extends upon most of the population, with a Christian heritage. The men interviewed in this research have illustrated their religious practices in a more institutionalized term in comparison to the women. In the feminine perspective, religion is experienced in a more personal terms. Violence against women is present, but considering an intersectional glance, a schizophrenic woman is more vulnerable to this type of aggression. The research concludes that the discursive practices of the participants interviewed have an emancipatory potential. They may produce counterdiscourses, the deconstruction and negotiation of the hegemonic power that tends to influence religion and biomedical practices. This may leads to the re-construction, redefinition of their identity positions in society.